Cultural Decentralization Within a Post Colonial Territory: Movements in Malaysia's Music Culture - Johan Othman, (Wacana Seni Journal of Arts Discourse, 2002)
Post-Colonized Malaysia acquired an identity that signifies a monolithic 'edifice' possessing attributes of a triadic sub-national/cultural foundation. However, the label 'Malaysian' is geared to signify a compromise of the sub-national characteristics for a good faith of formulating a national mass as a collective that is culturally centralized by an integration or common behaviors and reactions of a developing post-colonized territory.